2007
DOI: 10.1089/ham.2007.1031
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hypobaric Hypoxia (5486 m) Induces Greater Pulmonary HIF-1 Activation in Hilltop Compared to Madison Rats

Abstract: Compared to Madison strain Sprague-Dawley rats, the Hilltop strain is resistant to acute hypoxic pulmonary vasoconstriction and pulmonary leak, a pathology resembling high altitude pulmonary edema (HAPE) in humans. Hypoxia inducible transcription factor-1 (HIF-1) mediates transcription of proteins that can "rescue" tissue from hypoxia, including vasoactive and angiogenic proteins such as inducible nitric oxide synthase (iNOS) and vascular endothelial growth factor (VEGF). Because these proteins have theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Uncontrolled HIF activity can lead to endothelial cell dysfunction and pulmonary vascular leakage in vivo and in vitro (8,26,27). Our data showed that the knockdown of HIF-1a exerted a minimal effect on attenuating Hb-induced endothelial cell permeability.…”
Section: Tlr4 (mentioning
confidence: 65%
“…Uncontrolled HIF activity can lead to endothelial cell dysfunction and pulmonary vascular leakage in vivo and in vitro (8,26,27). Our data showed that the knockdown of HIF-1a exerted a minimal effect on attenuating Hb-induced endothelial cell permeability.…”
Section: Tlr4 (mentioning
confidence: 65%
“…In the exercise groups (in either hypoxia or normoxia), the rats walked for 48 h but were allowed to stop for 15-20 min every 4 h, so they could have access to food or water. It is important to note that the rats were, however, continuously exposed to hypoxia during 48 h. All procedures were performed in the main chamber that the investigator could access through an independently controlled antechamber where the pressure was set at 470.48 Torr (<3,800 m) [21]. When pressure inside the main chamber decreased to 3,800 m, the investigator could enter the main chamber to check the rats.…”
Section: Experimental and Control Groupsmentioning
confidence: 99%
“…The following procedure was performed in the main chamber with pressure equivalent to 3,800 m for investigators safety [21]. After anaesthesia (intraperitoneal injection of 10% chloral hydrate, 3 mg?kg -1 ; Sinopharm Chemical Reagent Co., Ltd, Shanghai, China), blood was quickly collected by direct puncture and sampling from the left ventricle using heparinised syringes.…”
Section: Arterial Blood Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron supplementation and iron chelation reduce and increase HPV respectively [ 69 , 70 ], possibly via altered HIF metabolism [ 71 ]. In two rat strains with differing pulmonary hypoxic responses, HIF-1 activity and HIF-mediated protein expression were higher in the strain with lesser pulmonary hypertension [ 72 ]. In contrast, mice with heterozygous HIF 1-alpha defi ciency have weaker acute and chronic hypoxic responses in isolated pulmonary vascular smooth myocytes and pulmonary vessels than wild type mice [ 73 , 74 ].…”
Section: Neuro-humoral Responsesmentioning
confidence: 99%